Anterior Cruciate Ligament Reconstruction in High School and College-Aged Athletes: Does Autograft Choice Influence Anterior Cruciate Ligament Revision Rates?. Issue 2 (February 2020) - ; Spindler, Kurt P.; Huston, Laura J.; Zajichek, Alexander; Reinke, Emily K.; Amendola, Annunziato; Andrish, Jack T.; Brophy, Robert H.; Dunn, Warren R.; Flanigan, David C.; Jones, Morgan H.; Kaeding, Christopher C.; et al.
Background: Physicians' and patients' decision-making process between bone–patellar tendon–bone (BTB) and hamstring tendon autografts for anterior cruciate ligament (ACL) reconstruction (ACLR) may be influenced by a variety of factors in the young, active athlete. Purpose: To determine the incidence of both ACL graft revisions and contralateral ACL tears resulting in subsequent ACLR in a cohort of high school– and college-aged athletes who initially underwent primary ACLR with either a BTB or a hamstring autograft. Study Design: Cohort study; Level of evidence, 2. Methods: Study inclusion criteria were patients aged 14 to 22 years who were injured in sports, had a contralateral normal knee, and were scheduled to undergo unilateral primary ACLR with either a BTB or a hamstring autograft. All patients were prospectively followed for 6 years to determine whether any subsequent ACLR was performed in either knee after their initial ACLR. Multivariable regression modeling controlled for age, sex, ethnicity/race, body mass index, sport and competition level, baseline activity level, knee laxity, and graft type. The 6-year outcomes were the incidence of subsequent ACLR in either knee. Results: A total of 839 patients were eligible, of which 770 (92%) had 6-year follow-up for the primary outcome measure of the incidence of subsequent ACLR. The median age was 17 years, with 48% female, and the distribution of BTB and hamstring grafts was 492 (64%) and 278 (36%), respectively. The incidence of subsequent ACLR at 6 years was 9.2% in the ipsilateral knee, 11.2% in the contralateral normal knee, and 19.7% for either knee. High-grade preoperative knee laxity (odds ratio [OR], 2.4 [95% confidence interval [CI], 1.4-3.9]; P = .001), autograft type (OR, 2.1 [95% CI, 1.3-3.5]; P = .004), and age (OR, 0.8 [95% CI, 0.7-1.0]; P = .009) were the 3 most influential predictors of ACL graft revision in the ipsilateral knee. The odds of ACL graft revision were 2.1 times higher for patients receiving a hamstring autograft than patients receiving a BTB autograft (95% CI, 1.3-3.5; P = .004). No significant differences were found between autograft choices when looking at the incidence of subsequent ACLR in the contralateral knee. Conclusion: There was a high incidence of both ACL graft revisions and contralateral normal ACL tears resulting in subsequent ACLR in this young athletic cohort. The incidence of ACL graft revision at 6 years after index surgery was 2.1 times higher with a hamstring autograft compared with a BTB autograft.